Paediatric chronic fatigue syndrome: Complex presentations and protracted time to diagnosis. Issue 11 (31st October 2013) - Knight, Sarah; Harvey, Adrienne; Lubitz, Lionel; Rowe, Kathy; Reveley, Colette; Veit, Frederike; Hennel, Sabine; Scheinberg, Adam
Abstract : Aim: The diagnosis and management of paediatric chronic fatigue syndrome (CFS) remain ongoing challenges for paediatric clinicians, particularly given its unknown aetiology and the little research on effective treatments for this condition. The aim of this study was to describe the presenting features of new patients attending a specialist chronic fatigue clinic at a tertiary‐level Australian children's hospital. Method: The medical records of all patients with an initial consultation at the chronic fatigue clinic over a 12‐month period were reviewed using a standardised data collection template. Functional impact was based on school attendance and classified according to the National Institute of Health and Clinical Excellence guidelines (2007). Results: A total of 99 patients attending the clinic were identified. Of these, 59 were diagnosed with CFS. Median age was 15.4 years with almost two‐thirds of patients of female sex. Median time between symptom onset and diagnosis was 15.5 months. There was a high occurrence of fatigue, sleep disturbance, pain, postexertional malaise, and autonomic and cognitive symptoms in the group. The functional impact of CFS was classified as mild for 20%, moderate for 66% and severe for 14% of patients. Conclusions: Most young people diagnosed with CFS experience symptoms for a protracted period, with considerable functional impact prior to initial tertiary service consultation. This audit has identified important areas for research, practice development and education in relation to the management of patients with CFS.